Incidence and characteristics of vitamin D deficiency rickets in New Zealand children: a New Zealand Paediatric Surveillance Unit study - Benjamin J. Wheeler; Nigel P. Dickson; Lisa A. Houghton; Leanne M. Ward; Barry J. Taylor (Australian and New Zealand Journal of Public Health, 2015)
Abstract Objective: To investigate the incidence and characteristics of vitamin D deficiency rickets in New Zealand (NZ). Methods: Prospective surveillance among paediatricians of Vitamin D Deficiency Rickets was conducted by the New Zealand Paediatric Surveillance Unit (NZPSU) for 36 months, from July 2010 to June 2013, inclusive. Inclusion criteria were: children and adolescents <15 years of age with vitamin D deficiency rickets (defined by low serum 25‐hydroxyvitamin D and elevated alkaline phosphatase levels, and/or radiological rickets). Results: Fifty‐eight children with confirmed vitamin D deficiency rickets were identified. Median age was 1.4 (range 0.3–11) years, 47% were male, and 95% of the children were born in NZ; however, the majority of the mothers (68%) were born outside NZ. Overall annual incidence of rickets in children aged <15 years was 2.2/100,000 (95%CI 1.4–3.5); with incidence in those <3 years being 10.5/100,000 (95%CI 6.7–16.6). Skeletal abnormalities, poor growth and motor delay were the most common presenting features, with hypocalcaemic convulsion in 16% of children. Key risk factors identified were: darker skin pigment, Indian and African ethnicity, age <3 years, exclusive breast feeding, and southern latitude, particularly when combined with season (winter/spring). Of the patients reported, none had received appropriate vitamin D supplementation. Conclusions: Vitamin D deficiency rickets remains a problem for NZ children. Key risk factors remain similar to those identified in the international literature. Preventative targeted vitamin D supplementation, as per existing national guidelines, was lacking in all cases reported. Implications: Vitamin D deficiency rickets is the most significant manifestation of vitamin D deficiency in growing children. To reduce the incidence of this disease among those at high risk, increasing awareness and implementation of current public health policies for targeted maternal, infant and child supplementation are required.